(untitled) (Research, Society and Development, 2022)
Introduction: In the context of pediatrics, cancer is considered a rare disease, yet in Brazil it is the second leading cause of mortality among children and adolescents. It is also noteworthy that cancer patients have a significant dental shortage, thus requiring prior attention to cancer treatment. Objective: To describe and discuss the findings in the literature regarding oral manifestations in pediatric cancer patients. Methodology: Literature review, of an integrative nature, with the data being summed in a qualitative way. The sample collected to support this review work was obtained through the CAPES, SCIELO, MEDLINE, LILACS, BBO, SCOPUS, Google Scholar, and PubMed Journals Portal databases. Results: Antineoplastic treatment has the ability to induce cell damage in the epithelium, oral mucosa and salivary gland structures, impairing their functions and, consequently, promoting changes, which manifest as stomatological complications in cancer patients. The main alterations are oral mucositis, osteoradionecrosis, opportunistic infections such as candidiasis, xerostomia, herpes and gingival bleeding. Final considerations: The reported oral manifestations can be avoided and/or minimized, through the performance of a multidisciplinary team, where the insertion of the Dental Surgeon in the clinical management of the patient is essential.